Aonla-Based Hortipastoral System for Soil Nutrient Buildup and Profitability - Kumar, Sunil; Kumar, Sudhir; Choubey, B K (Annals of Arid Zone, 2016)
Abstract: Aonla-based hortipastoral slstem involving Dichanthium annulatum with four nitrogen doses viz., 0, 20, 40 and 60 kg ha- to the grass as understory forage species was studied for ten consecutive years (1996-2005). Highest dose of N (60 kg ha-1) gave significantly higher dry pasture yield (4.04 t ha-1 ) with aonla tree compared with the pure pasture condition (3.73 t ha-1 ). The pasture production was marginally higher in association with trees (3.38 t DM ha-1) as compared to pure pasture (3.07 t DM ha-1). The fruit production started from 5th year of planting and over the five years of fruiting maximum fruit production of 13.25 t ha-1 was recorded when 60 kg N ha-1 was applied to the grass component. 40-60 kg N ha-1 applied to grass plot improved psysico-chemical composition of fruits. The mean B:C ratio over ten year of experiment was 1:1.85 for pure pasture and 1:3.70 for hortipastoral system. The employment generation was 2.07-man-days month-1 in pure pasture and 4.74-man-days month-1 with incorporation- of aonla tree with the same pasture. Key words: Aonla cv. N.A.-7, Dichanthium annulatum, nitrogen, economics, employment.